Floral Regulation: The Significant Virtue of Horticultural Flowering Plants - Faiza Shafique Khan; Chong-Yang Ning; Zhuang-Zhuang Li; Chun-Gen Hu; Jin-Zhi Zhang (Horticulturae)
Flowering is a complex developmental mechanism and is essential for successful reproduction in plants. Complex regulatory networks transform vegetative shoot apical meristems into inflorescence meristems. Further, floral meristems transition to floral bud outgrowth and flowering. Floral regulatory pathways are independently involved in flowering, and most of what we know about genetic regulation comes from model plants. Despite the advancements in plant development biology, the understanding of molecular mechanisms and floral signals in horticultural plants is complex. Studies on gene regulatory mechanisms provide a global view of flowering in horticultural plants. In this paper, we discuss the flowering pathways converging on complex gene regulatory mechanisms and summarize the recent findings in horticultural plants in order to help us understand how they regulate flowering and provide an update for future research.